Predictors of Language Dominance: An Integrated Analysis of First Language Attrition and Second Language Acquisition in Late Bilinguals - Schmid, Monika S.; Yılmaz, Gülsen (Frontiers in Psychology, 2018)
Late bilinguals who spend (part of) their adult lives in an environment where a language other than the one they learned in childhood is spoken typically experience a range of language development phenomena. Most obviously, they will acquire some level of receptive and/or productive knowledge of the new, or second, language (L2). How basic or advanced that level will be is determined by a range of environmental, experiential, attitudinal and individual factors. Secondly, they will most likely find the knowledge of their native language (L1) beginning to diverge from that of monolingual speakers in their country of origin, a process known as language attrition. In the course of this developmental process, some L2 skills may eventually match or even overtake the corresponding skill in the L1. This shift in the balance between L1 and L2 is the focus of investigations of language dominance. The present study explores language dominance in four migrant populations (Germans in the Netherlands and Canada, Turks and Moroccans in the Netherlands). Investigating both the development of formal/controlled skills and more automatic aspects of lexical access and fluency, we aim to attain a better understanding of how extralinguistic factors contribute to the development of both languages. We argue that an integrated perspective can contribute more profound insights into the predictors of this complex process of bilingual development. In particular, our findings show that statistical models based on linear relationships fall short of capturing the full picture. We propose an alternative method of analysing data, namely discriminant function analysis, based on a categorisation of the populations and demonstrate how this can enhance our understanding. Our findings suggest that different aspects of the bilingual experience contribute differently to language development, regardless of language combination and type of skill measured. Contrary to what previous research suggests, measures relating to the intensity of informal use of both the L1 and the L2 in daily life are important in determining whether someone is a good or a poor L1 maintainer, while high vs. low success in acquisition appears to be predominantly associated with personal factors such as educational level.